Design and psychometric evaluation of the breast cancer screening behaviors scale based on the health action model (HAM) - Fahimeh Mahboobighazaani; Masoud Karimi; Mojtaba Azadbakht; Leila Ghahremani (BMC, 2022)
Abstract Background Breast cancer is known as the most common cancer and the first-rank malignancy among women. Screening plays a crucial role in early diagnosis and timely treatment. This paper presents the results of design, evaluation and analysis of a questionnaire based on the health action model to investigate breast cancer screening behaviors and their relevant factors. Methods The study is based on using a combination of quantitative and qualitative approaches for optimal design and development of research tools. In order to design the structure of the health action model and screening behaviors related factors, both qualitative methods such as semi-structured interviews and quantitative approaches studied. Psychometric properties of the research tool were investigated through literature review. The research population consisted of 210 30-69 years old females based in Kashan who were selected through simple random sampling. The relative and content validity indexes were calculated to judge the content of the tool. Also, the confirmatory factor analysis was used to evaluate the construct validity. Additionally, intra-class correlation coefficient and Cornbrash's alpha coefficient were calculated to evaluate the reliability of the instrument. The data were analyzed using the SPSS 22 and AMOS 22 software packages. Results The mean age of the participants was 43 ± 9.82 Years old. The final version of the questionnaire was prepared in four sections, namely demographic factors (15 items), knowledge (12 items), constructs of the health action model or the factors related to breast cancer screening behaviors (67 items), and behavior (6 items). Factor analysis confirmed that the health action model fits in measuring breast cancer screening behaviors. Conclusion The tool designed for measuring breast cancer screening behaviors showed acceptable psychometric properties amongst females and can be used as a valid tool in conducting research in health studies.